Molecular evidence of genome editing in a mouse model of immunodeficiency - Abdul-Razak, Hayder; Gabriel, Richard; Bartholomä, Cynthia C.; Kalle, Christof von; Schmidt, Michael (Scientific reports, 2018)
Genome editing is the introduction of directed modifications in the genome, a process boosted to therapeutic levels by designer nucleases. Building on the experience of ex vivo gene therapy for severe combined immunodeficiencies, it is likely that genome editing of haematopoietic stem/progenitor cells (HSPC) for correction of inherited blood diseases will be an early clinical application. We show molecular evidence of gene correction in a mouse model of primary immunodeficiency. In vitro experiments in DNA-dependent protein kinase catalytic subunit severe combined immunodeficiency (Prkdc scid) fibroblasts using designed zinc finger nucleases (ZFN) and a repair template demonstrated molecular and functional correction of the defect. Following transplantation of ex vivo gene-edited Prkdc scid HSPC, some of the recipient animals carried the expected genomic signature of ZFN-driven gene correction. In some primary and secondary transplant recipients we detected double-positive CD4/CD8 T-cells in thymus and single-positive T-cells in blood, but no other evidence of immune reconstitution. However, the leakiness of this model is a confounding factor for the interpretation of the possible T-cell reconstitution. Our results provide support for the feasibility of rescuing inherited blood disease by ex vivo genome editing followed by transplantation, and highlight some of the challenges.